Pelatihan Geogebra Sebagai Media Pembelajaran Matematika Pada Guru-Guru SMP di Kota Mataram Tahun 2021 - Amrullah Amrullah; Nilza Humaira Salsabila; Junaidi Junaidi; Hapipi Hapipi; Sudi Prayitno (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
In the 2019 survey, 82.2% of teachers never participated in media training, especially learning media based on geogebra technology. Meanwhile, 92.8% of teachers stated that mathematics requires learning media. The low quality of education in NTB requires special attention from both the government and the private sector, so it is important to conduct technology-based learning media training in order to improve the quality of education, especially improving the quality of teachers. The training was carried out using offline and online methods for two days, 19 and 20 August 2021 at SMPN 16 Mataram. The training was attended by 22 participants from junior high school mathematics teachers in the city of Mataram. In the implementation of the training, an evaluation was carried out using questionnaires and observations. The conclusions from the results of the service were as follows: Geogebra training as a medium for learning mathematics for SMP teachers in the city of Mataram in 2021 received a very good response and was well received by the teachers. Geogebra training as a medium for learning mathematics for junior high school teachers in the city of Mataram in 2021 is very in line with what is expected by mathematics teachers in the City of Mataram and increases teacher competence in the context of applying technology in learning to develop technology-based mathematics learning media.